Inflammatory breast cancer: Clinical implications of genomic alterations and mutational profiling - Faldoni, Flávia L. C.; Villacis, Rolando A. R.; Canto, Luisa M.; Fonseca-Alves, Carlos E. [UNESP]; Cury, Sarah S. [UNESP]; Larsen, Simon J.; Aagaard, Mads M.; Souza, Cristiano P.; Scapulatempo-Neto, Cristovam; Osório, Cynthia A. B. T.; Baumbach, Jan; Marchi, Fabio A.; et al. (MDPI, 2020)
Inflammatory breast cancer (IBC) is a rare and aggressive type of breast cancer whose molecular basis is poorly understood. We performed a comprehensive molecular analysis of 24 IBC biopsies naïve of treatment, using a high-resolution microarray platform and targeted next-generation sequencing (105 cancer-related genes). The genes more frequently affected by gains were MYC (75%) and MDM4 (71%), while frequent losses encompassed TP53 (71%) and RB1 (58%). Increased MYC and MDM4 protein expression levels were detected in 18 cases. These genes have been related to IBC aggressiveness, and MDM4 is a potential therapeutic target in IBC. Functional enrichment analysis revealed genes associated with inflammatory regulation and immune response. High homologous recombination (HR) deficiency scores were detected in triple-negative and metastatic IBC cases. A high telomeric allelic imbalance score was found in patients having worse overall survival (OS). The mutational profiling was compared with non-IBC (TCGA, n = 250) and IBC (n = 118) from four datasets, validating our findings. Higher frequency of TP53 and BRCA2 variants were detected compared to non-IBC, while PIKC3A showed similar frequency. Variants in mismatch repair and HR genes were associated with worse OS. Our study provided a framework for improved diagnosis and therapeutic alternatives for this aggressive tumor type.
Keywords: Copy number alterations; Gene variants; Genomic scars; Homologous recombination deficiency; Inflammatory breast cancer; Microarray